Tecnologia e subjetividade: a trama enunciativa nos textos normativos da SEED/PR - Coelho, Anderson Germano (2025)
During the COVID-19 pandemic, the Paraná State Department of Education (SEED/PR) implemented digital platforms to ensure the continuity of education, regulating their use through normative texts (laws, decrees, resolutions, and official documents) linked to educational goals. This measure accelerated technological adoption, impacting school structures and teaching routines while also fostering debates about the future of education. It is believed that these texts, as part of institutional discourse, despite their intrinsic characteristic of a certain neutrality marked by the erasure of the enunciator (objectifying orientation), also implicitly convey positions regarding technology and education. Thus, this study aims to investigate the presence of a point-of-view (POV) in SEED/PR’s normative texts on the use of digital educational platforms, analyzing the role of the textual enunciator (ET) in discourse organization and enunciative positioning. To achieve this, four documents published between 2021 and 2023 will be analyzed (an official document, a law, a decree, and a resolution), establishing the following specific objectives: (a) to examine the enunciative stances and POVs present in the selected texts; (b) to describe the forms of ET’s manifestation in normative texts; and (c) to contribute to the understanding of enunciative dynamics in these texts, highlighting their implications for the construction of style and authorship. The study concludes that even in institutional discourses, there are marks of enunciative positioning, challenging the notion of objectivity often associated with such texts. This occurs because the ET, although erased, plays an active role in discourse organization and in guiding the POV, promoting the construction of a macro-POV that directs the reader’s interpretation.